2008
DOI: 10.1038/onc.2008.199
|View full text |Cite
|
Sign up to set email alerts
|

Parkin as a tumor suppressor gene for hepatocellular carcinoma

Abstract: The parkin was first identified as a gene implicated in autosomal recessive juvenile Parkinsonism. Deregulation of the parkin gene, however, has been observed in various human cancers, suggesting that the parkin gene may be important in tumorigenesis. To gain insight into the physiologic role of parkin, we generated parkinÀ/À mice lacking exon 3 of the parkin gene. We demonstrated here that parkinÀ/À mice had enhanced hepatocyte proliferation and developed macroscopic hepatic tumors with the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
168
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(177 citation statements)
references
References 49 publications
9
168
0
Order By: Relevance
“…We, recently, reported that Parkin-deficient mice lacking exon 3 of the Parkin gene are susceptible to liver carcinogenesis, providing the first evidence that Parkin is a tumor suppressor gene. 19 Consistent with our findings, a high frequency of loss of heterozygosity or deletions spanning the Parkin gene has been detected in various human cancers. [9][10][11][12][13][14][15][16][17][18] In the present study, we demonstrated that Parkin expression is induced in response to growth signaling, and is involved in the proteolytic degradation of cyclin E protein in colonic epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We, recently, reported that Parkin-deficient mice lacking exon 3 of the Parkin gene are susceptible to liver carcinogenesis, providing the first evidence that Parkin is a tumor suppressor gene. 19 Consistent with our findings, a high frequency of loss of heterozygosity or deletions spanning the Parkin gene has been detected in various human cancers. [9][10][11][12][13][14][15][16][17][18] In the present study, we demonstrated that Parkin expression is induced in response to growth signaling, and is involved in the proteolytic degradation of cyclin E protein in colonic epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…[16][17][18] We recently demonstrated that Parkin-deficient mice lacking exon 3 of the Parkin gene developed hepatocellular carcinoma, whereas Parkin -/-mice were neurologically normal with no obvious neuropathologic changes. 19 Further, the loss of Parkin expression contributes to the overproliferation of hepatocytes leading to hepatomegaly, suggesting a critical role for Parkin in the regulation of hepatocyte proliferation. 19 These observations suggest that Parkin has a role as a tumor suppressor and may be involved in cell cycle regulation in epithelial cells.…”
Section: Uiccmentioning
confidence: 99%
See 2 more Smart Citations
“…Parkin KO mice have previously been shown to have increased proliferation leading to the eventual development of hepatocellular carcinoma at 18 months (32,33). Therefore, we evaluated proliferation levels in WT and Parkin KO mice after APAP treatment to determine whether greater levels of hepatocyte proliferation could be an additional mechanism of protection against APAPinduced liver injury in KO mice.…”
Section: Parkin Ko Mice Had Decreased Jnk Activation and Increased MCmentioning
confidence: 99%